A relação dialógica na prática clínica do profissional fisioterapeuta e a visão integral do sujeito-paciente - Zanotelli, Germana Albuquerque Costa (2015)
Understanding the biopsychosocial aspects of the subjects who seek health care emerges as a character tied to good practice. In this context we present the practice of physiotherapist whose training has remnants of biomedical conception of health education characterized by strong focus on disease rather than the subject that presents. We consider the dialogic relationship that occurs during physical therapy important element in mediation for understanding the entirety of the subject-patient. The research The dialogical relationship in clinical practice of the physiotherapist and the full view of the subject-patient, aims to understand how does the dialogic relational communicability in practice this professional physiotherapy for the identification of subjective and objective aspects that establish a comprehensive view of the subject -patient. It is therefore a scientific qualitative study with a phenomenological hermeneutic dialectic approach. The research field is the University of Fortaleza - UNIFOR. The sources used in the research were: graduates of UNIFOR physiotherapists, physiotherapy course coordinator of that institution and official documents governing the profession. Evidence collection techniques were: document analysis and reflective interview. The survey results indicate that the dialogue that happens during clinical practice in Physiotherapy set up time that favors the understanding of the subject-patient and their context. But this understanding does not outweigh the importance of the physical component sets during treatment. Thus, with a view to rehabilitating the subject-patient, the therapist makes use of scientific expertise for this purpose. The given initial thesis: the physiotherapist relationship / subject-patient, there is evidence of the appreciation of intersubjectivity with a strong presence of clinical behaviors that favor the physical body is not experiencing a communicability that overcomes the body dichotomy / mind, was partially confirmed by the data and analyzes. We conclude that the speeches of the subjects of this research announced an awareness of the understanding of the subjective aspects of the subjects-patients still showing the importance of the perspective of integral vision of the same from the intersubjectivity. We note, therefore, not only evidence but statements about that only the use of targeted behavior for functionality not cope with the demand of care within the practice in Physiotherapy and communicability exercised during clinical practice promotes the development of understanding of biopsychosocial dimensions of those who looks for treatment.